Decision Support System for The Provision of Umrah Packages with AHP and MOORA Methods - Naurah Huwaida (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
The COVID-19 pandemic had a major influence that forces several business entities in various types of sectors to take various ways in order to maintain business continuity. This is no exception also affects business entities in the tourism sector. Travel restrictions during this pandemic have an impact on the sales of conventional travel agents. However, that doesn’t mean that conventional travel agents just disappear. Several travel agents can still exist, one of them is Bella Hamed Tour, which is a travel agent for Umrah. The qualified service they have all this time has made Bella Hamed Tour earn the trust of consumers, even in the midst of pandemic. However, the pandemic situation also makes Bella Hamed Tour need to make adjustments in making Umrah packages that required to be planned through consideration of the best decisions. Therefore, a decision support system is needed to assist the management of Bella Hamed Tour quickly arrange the Umrah package. The method applied in the decision support system is the Analytical Hierarchy Process (AHP) for weighting the criteria and Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) for ranking the results of the decision selection. Making a decision support system executed in form of a website.